SEEING THE AGREEMENT OF THE RESIDENTS IN FILLING EMPTY SPACE IN THE SETTLEMENT - Erza Rahma Hajaty; Rona Fika Jamila; Ika Riski Laela Wati (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2021)
Land availability is increasingly limited, so it is not surprising that land prices are getting more expensive. However, behind the high price of land, there is a lot of empty space, especially in settlements, in the form of vacant land, buildings, ready-to-build land and built-up land that is not utilized or stalled. There are houses in settlements that are purchased only for investment so that they are not used or occupied by the owner, vacant land such as land under a network of sutets, and land in the form of lots ready to build in unsold housing. This condition is of course very unfortunate given the high price of land and the very high needs of the community for land, especially for housing, social space and as a place of business. Therefore, this research is to see how the occupants agree to fill the empty space in the settlement, using qualitative methods. The results showed that most residents agree that empty spaces in settlements should not be left empty for too long, but can be used for useful things while maintaining public interests, not harming others, not disturbing others, positive activities. and keep the environment clean. The use of empty space in settlements, both formal and non-formal by residents of the premises, is as a place to raise fish, place animal cages, plant fruit and vegetable gardens, park vehicles, play areas for children, place temporary leaf trash, sports fields and night markets.